2018
DOI: 10.1002/jcp.26364
|View full text |Cite
|
Sign up to set email alerts
|

Effects of small interfering RNA targeting TLR4 on expressions of adipocytokines in obstructive sleep apnea hyponea syndrome with hypertension in a rat model

Abstract: We explored the effects of RNA interference-mediated silencing of TLR4 gene on expressions of adipocytokines in obstructive sleep apnea hyponea syndrome (OSAS) with hypertension in a rat model. Systolic blood pressure of caudal artery and physiological changes were observed when establishing rat models of OSAS with hypertension. Mature rat adipocytes were induced from separated and cultured primary rat adipocytes. To transfect rat mature adipocytes, TLR4 siRNA group and negative control (NC) siRNA group were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Toll-like receptor 4 (TLR4), a typical representative of pattern recognition receptors in innate immune responses, plays an important role in activation of inflammation in atherosclerosis. It has been recently demonstrated that IHR accelerated growth and vulnerability of atherosclerotic plaque, which probably acted by triggering the activation of TLR4/NF-κB signaling [4][5][6][7]. Acting as both up-stream and down-stream mediators of TLR signaling, tumor necrosis factor (TNF)-α has been shown to be upregulated in OSA patients, and this increase became more pronounced with the more severe grades of OSAS, indicating that TNF-α might be a promising circulating biomarker for the development of OSA [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Toll-like receptor 4 (TLR4), a typical representative of pattern recognition receptors in innate immune responses, plays an important role in activation of inflammation in atherosclerosis. It has been recently demonstrated that IHR accelerated growth and vulnerability of atherosclerotic plaque, which probably acted by triggering the activation of TLR4/NF-κB signaling [4][5][6][7]. Acting as both up-stream and down-stream mediators of TLR signaling, tumor necrosis factor (TNF)-α has been shown to be upregulated in OSA patients, and this increase became more pronounced with the more severe grades of OSAS, indicating that TNF-α might be a promising circulating biomarker for the development of OSA [8].…”
Section: Introductionmentioning
confidence: 99%
“…To investigate the protective effect of miR-21-5p on overt inflammation and cell injury, we first evaluated whether miR-21-5p mimic had inhibitory effects on several predicted target genes in THP-1 cells under NOX condition. miR-21-5p mimic at different concentrations(1,5,10,25, and 50 nM, respectively) enhanced miR-21-5p gene expressions(Figure 3a, versus 0 nM, all p-values < 0.05) in a dose-dependent manner, while inhibited TNF-α (Figure 3b, versus 0 nM, all p-values < 0.05), IL-6R (Figure 3c, versus 0 nM, all p-values < 0.05), and TLR4 (Figure 3d, versus 0 nM, all p-values < 0.05) gene expressions in a dose-dependent manner.…”
mentioning
confidence: 99%
“…In this study, chronic intermittent hypoxia (CIH) was used to construct an OSA model. The induction principle of OSA-related diseases, including metabolic dysfunction-associated steatotic liver disease, was based on OSA-induced chronic hypoxia [ 21 23 ]. OSA could decrease O 2 inhalation directly.…”
Section: Methodsmentioning
confidence: 99%
“…During the modeling process, the cage was filled with nitrogen to reduce the oxygen concentration so that the animals were in an anoxic environment, and then the cage was filled with oxygen or air to simulate the resumption of ventilation of the animals. Similar to the occluding endotracheal intubation model under general anesthesia, this model could simulate different degree of AHI by setting the duration and cycle of hypoxia ventilation and simulate the duration of OSA patients by setting the duration of the experiment ( 5 28 ). A typical molding process is shown in Figure 1 .…”
Section: Characteristics Advantages and Limitations Of Existing Osa A...mentioning
confidence: 99%